La frontera eficiente y los límites de inversión para las AFP: una nueva mirada - Ortiz, Diana (2010)
This article provides a re-estimation of the pension plan funds administrators’ efficient frontier. The goal here is two-fold: on the one hand it measures the effect of investment limits imposed by regulators. Unlike previous studies, here the short positions are not limited; this assumption is based upon the completeness of the financial markets: when the markets are completed, any financial instrument may be replicated. On the other hand, this article measures the performance of the pension plan funds. In earlier works, the performance was measured as the difference between the profitability in the frontier and the one obtained at the level of a given risk; here the return is measured as the relationship of optimal risk profitability and the one obtained. The main conclusion drawn is that regulation supports the high level of risks taken by the administrators.